La seguridad jurídica y el debido proceso en las audiencias virtuales en la Corte Provincial de Justicia de Chimborazo. - Barrionuevo Pomboza, Estefanía Elizabeth (2023)
Information and Communication Technologies (ICT) are important resources in the hearings of jurisdictional units. The problem in the virtual hearings of the Provincial Court of Justice of Chimborazo is the violation of due process and the right to legal security. The objective was to determine if the virtual hearings developed in the Provincial Court of Justice of Chimborazo observe the guarantees of due process and the right to legal security. The methodology is framed in the non-experimental design. The phenomena are studied according to how they are presented in the virtual processes. The population was: 14 free practice lawyers and 6 judges of the Provincial Court of Justice of Chimborazo. The results demonstrated that legal security and due process in virtual hearings have been violated. They also consider that ICTs are necessary tools in virtual hearings, so technology is not ruled out in these judicial processes. The conclusion expresses the need to modify and adapt the respective laws in virtual hearings. The judges are responsible for ensuring and guaranteeing due process and legal security during the development of the same. The development of virtual hearings in the Provincial Court of Justice of Chimborazo was legally analyzed. It was found that there is a violation of the rights to legal certainty and due process.